Global Decline of Insects - Abdel Farag El-Shafie, Hamadttu (IntechOpen, 2022)
Insects are a group of animals that contribute significantly to the proper functioning of different ecosystems on the planet. They provide services such as pollinating crops, recycling nutrients and controlling pests. Many scientific publications and reports have studied the current global decline of insects. This decline can severely affect other groups of animals including birds, reptiles, amphibians, fish, and small mammals that utilize insects as a source of food. This will have a great impact on the trophic cascade and an eventual adverse effect on the overall ecosystem. This book provides insights into the possible reasons behind the decline of insects as well as potential measures that might mitigate this decline. It contains eleven chapters written by different experts. The book is useful for a wide range of readers including entomologists, ecologists, botanists, environmentalists, and amateurs who love collecting and preserving insects.